2009
DOI: 10.1051/0004-6361/200810962
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic variability of the circumstellar disk of the Be starζTauri

Abstract: Context. About 2/3 of the Be stars present the so-called V/R variations, a phenomenon characterized by the quasi-cyclic variation in the ratio between the violet and red emission peaks of the H i emission lines. These variations are generally explained by global oscillations in the circumstellar disk forming a one-armed spiral density pattern that precesses around the star with a period of a few years. Aims. This paper presents self-consistent models of polarimetric, photometric, spectrophotometric, and interf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
165
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(187 citation statements)
references
References 39 publications
19
165
0
3
Order By: Relevance
“…It is known that companions can influence the circumstellar disks of Be stars in several ways: affecting the global disk oscillations (Oktariani & Okazaki 2009), truncating the outer disk (Carciofi et al 2009), and even extracting material from the central star in eccentric orbits (Miroshnichenko et al 2001;Kervella et al 2008). The latter authors found that the orbital period of the close companion of Achernar (HD 10144) appears similar to the observed pseudo-periodicity of the Be phenomenon, indicating that an interaction between the components at periastron could be triggering the Be episodes.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that companions can influence the circumstellar disks of Be stars in several ways: affecting the global disk oscillations (Oktariani & Okazaki 2009), truncating the outer disk (Carciofi et al 2009), and even extracting material from the central star in eccentric orbits (Miroshnichenko et al 2001;Kervella et al 2008). The latter authors found that the orbital period of the close companion of Achernar (HD 10144) appears similar to the observed pseudo-periodicity of the Be phenomenon, indicating that an interaction between the components at periastron could be triggering the Be episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Major outbursts might temporarily lead to such a situation but the cyclic variability would probably require them, too, to be cyclic. A perturbation that propagates in a spiral-like pattern has a physical foundation in global m = 1 disk oscillations, which will be developed into a fully self-consistent model in Paper II (Carciofi et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Electron scattering modified by pre-or postscattering absorption by hydrogen atoms in the disk produces the characteristic wavelength-dependent polarization signature of Be stars (Wood et al 1996a(Wood et al , 1996b. Modeling such data yields information about the density in the inner region of these disks (Wood et al 1997;Carciofi et al 2009) and has been used, along with interferometric observations, to confirm that the disks are geometrically thin (Quirrenbach et al 1997). …”
Section: Disk-loss and Disk-renewal Phases In Classical Be Stars I mentioning
confidence: 99%